Development of the argumentative capacity of dental students using a virtual educational forum - Fernández-Jacinto, Leila (2023)
A virtual discussion forum was used as a didactic resource for developing argumentative skills in dental students in the occlusion course. The forum was applied as a replacement for the weekly evaluations intended to assess whether the students knew the concepts taught in each master class. Forty-eight students participated, and the variables of the virtual discussion forum and argumentative capacity were analyzed. The result was that the virtual forum used as a didactic resource influenced the argumentative capacity of the students. This finding agrees with several studies carried out in basic education as well as in university education. It is concluded that the discussion forum applied contributes to the development of cognitive abilities, specifically those related to argumentation.